2020
DOI: 10.3389/fonc.2020.00858
|View full text |Cite
|
Sign up to set email alerts
|

MTFR2 Promotes the Proliferation, Migration, and Invasion of Oral Squamous Carcinoma by Switching OXPHOS to Glycolysis

Abstract: MTFR2 is an oncogene involved in the progression of cancer, its' potential mechanism in oral squamous carcinoma remains unknown. The aim of this study was to uncover the bio-function and the mechanism of MTFR2 in the progression of oral squamous carcinoma. We scanned TCGA database to identify MTFR2 as dysregulated genes. qRT-PCR and Western blotting assays were applied to detect the expression pattern of MTFR2 in oral squamous carcinoma. We next established stable MTFR2-overexpressing and MTFR2 knocking down c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…APE1 methylation deletion reduces mitochondrial translocation and increases mitochondrial DNA damage and cytochrome c release after stimulation, indicating that APE1 methylation promotes mitochondrial translocation and protects cells from oxidative damage. Previous studies have found that MTFR2 plays an oncogene role in BC and oral squamous cell carcinoma [11,12]. The authors' results using the Simple Modular Architecture Research Tool data resource illustrated that the level of MTFR2 methylation is significantly abnormal in HCC tissues.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…APE1 methylation deletion reduces mitochondrial translocation and increases mitochondrial DNA damage and cytochrome c release after stimulation, indicating that APE1 methylation promotes mitochondrial translocation and protects cells from oxidative damage. Previous studies have found that MTFR2 plays an oncogene role in BC and oral squamous cell carcinoma [11,12]. The authors' results using the Simple Modular Architecture Research Tool data resource illustrated that the level of MTFR2 methylation is significantly abnormal in HCC tissues.…”
Section: Discussionmentioning
confidence: 85%
“…Wang et al found that MTFR2 converts oxidative phosphorylation into glycolysis, thus promoting the growth, migration and infiltration of cancer cells [12]. The mechanism linked to the growth of HCC has not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is involved in regulation of proliferation of glioma stem cells (GSCs) and thus may affect the prognosis of glioblastoma (9,17). Most recently, MTFR2 has been reported to promote the proliferation, migration, and invasion of oral squamous carcinoma (21), and MTFR2-dependent regulation of TTK was involved in maintaining GSCs in glioblastoma and might serve as a potential novel druggable target for glioblastoma. It might regulate the expression of TTK for participation in up-regulation and expression of GSCs in glioblastoma.…”
Section: Discussionmentioning
confidence: 99%